An Analysis of Errors in the Indonesian Enhanced Spelling System (EYD) in Students’ Explanatory Writing - Gloria Eveline Talan; Andarini Cahyaningtyas (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Writing ability is an essential component of primary education, as it enables students to develop communication skills, critical thinking, and the capacity to express ideas effectively. This study aims to analyze errors in the use of the Indonesian Enhanced Spelling System (EYD) in explanatory text writing among fifth-grade students at SD Negeri Manyaran 01. A descriptive qualitative approach was employed to objectively and systematically describe the observed phenomena. The research participants consisted of 28 students from class VB. Data were collected through observation, interviews, and documentation. Data trustworthiness was ensured through source triangulation, method triangulation, peer debriefing, and repeated reading of the data. The findings indicate that the most frequent errors involve the incorrect use of capital letters that do not comply with EYD conventions. These errors are attributed to students’ limited understanding of spelling rules, lack of regular writing practice, and low reading interest. The findings emphasize the importance of improving writing instruction strategies and strengthening language literacy at the primary level so that students can write accurately in accordance with standard Indonesian language conventions.